Establishment and Evaluation of a Loop-Mediated Isothermal Amplification Assay for Rapid Detection of Pseudomonas fluorescens in Raw Milk - Bu, Yushan; Qiao, Wenjun; Zhai, Zhengyuan; Liu, Tongjie; Gong, Pimin; Zhang, Lanwei; Hao, Yanling; Yi, Huaxi (Frontiers in Microbiology, 2022)
Raw milk is susceptible to microbial contamination during transportation and storage. Pseudomonas fluorescens producing heat-resistant enzymes have become the most common and harmful psychrophilic microorganisms in the cold chain logistics of raw milk. To rapidly detect P. fluorescens in raw milk, the protease gene aprX was selected as detection target to construct a set of primers with strong specificity, and a loop-mediated isothermal amplification (LAMP) assay was established. The detection thresholds of LAMP assay for pure cultured P. fluorescens and pasteurized milk were 2.57 × 102 CFU/mL and 3 × 102 CFU/mL, respectively. It had the advantages over conventional method in low detection threshold, strong specificity, rapid detection and simple operation. This LAMP assay can be used for on-line monitoring and on-site detection of P. fluorescens in raw milk to guarantee the quality and safety of dairy products.